2020
DOI: 10.1039/c9fo03003d
|View full text |Cite
|
Sign up to set email alerts
|

The protective mechanism ofLactobacillus plantarumFZU3013 against non-alcoholic fatty liver associated with hyperlipidemia in mice fed a high-fat diet

Abstract: Lactobacillus plantarum FZU3013, isolated from the traditional brewing process of Hongqu rice wine, has beneficial effects on improving lipid metabolism disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 60 publications
4
35
0
1
Order By: Relevance
“…Obesity and hyperglycemia induced by an HFD were closely associated with the gut microbiota dysbiosis, which has been confirmed in this study. In addition, recent researches have also demonstrated that probiotics intervention exhibited promising roles, such as antiobesity and insulin sensitivity by restoring the balance of the intestine microorganisms in murine models (24,33). In this study, B2 intervention decreased the α-diversity in comparison with the HFD group, indicating that B2 characteristically altered the gut bacterial community.…”
Section: Discussionsupporting
confidence: 51%
“…Obesity and hyperglycemia induced by an HFD were closely associated with the gut microbiota dysbiosis, which has been confirmed in this study. In addition, recent researches have also demonstrated that probiotics intervention exhibited promising roles, such as antiobesity and insulin sensitivity by restoring the balance of the intestine microorganisms in murine models (24,33). In this study, B2 intervention decreased the α-diversity in comparison with the HFD group, indicating that B2 characteristically altered the gut bacterial community.…”
Section: Discussionsupporting
confidence: 51%
“…Steatosis and TG accumulation in liver tissue were reduced, and glycogen content in liver tissue was increased by administering MG4296 and MG5012. In a previous study, L. plantarum FZU3013 improved NAFLD and hyperlipidemia in mice fed an HFD [57]. L. GG improved hepatic steatosis in HFD-induced mice [58].…”
Section: Discussionmentioning
confidence: 76%
“…In general, patients with dyslipidemia also suffer from nonalcoholic fatty liver disease (NAFLD), and clinical manifestations include excessive accumulation of lipids, including TG and FAs, in hepatocytes [68]. Previous studies suggested that the gut microbiome is involved in the development of dyslipidemia and NAFLD [69], whereas the intestine and liver are intrinsically linked and strongly interdependent in metabolic functions [70,71]. For example, common buckwheat consumption significantly improved physiological indexes and biochemical parameters related to dyslipidemia and NAFLD in mice fed with an HFD.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%